Phân tích đa thức thành d) x^2 – 2xy +x – 2y f) x^3 – y^3 + 2x^2 + 2xy g) x^5 + x + 1

Phân tích đa thức thành
d) x^2 – 2xy +x – 2y
f) x^3 – y^3 + 2x^2 + 2xy
g) x^5 + x + 1

2 bình luận về “Phân tích đa thức thành d) x^2 – 2xy +x – 2y f) x^3 – y^3 + 2x^2 + 2xy g) x^5 + x + 1”

  1. d, x^2-2xy+x-2y
    =x(x-2y)+(x-2y)
    =(x-2y)(x+1)
    f,
    x^3+y^3+2x^2+2xy
    =(x+y)(x^2-xy+y^2)+2x(x+y)
    =(x+y)(x^2-xy+y^2+2x)
    x^3-y^3+2x^2-2xy
    =(x-y)(x^2+xy+y^2)+2x(x-y)
    =(x-y)(x^2+xy+y^2+2x)
    g, x^5+x+1
    =x^5-x^2+x^2+x+1
    =x^2(x^3-1)+(x^2+x+1)
    =x^2(x-1)(x^2+x+1)+(x^2+x+1)
    =(x^2+x+1)[x^2(x-1)+1]
    =(x^2+x+1)(x^3-x^2+1)
    $#congtrinhayp$

    Trả lời
  2. Giải đáp:
     ↓↓
    Lời giải và giải thích chi tiết:
    d) x^2 – 2xy +x – 2y
    =x(x-2y)+(x-2y)
    =(x-2y)(x+1)
    f)x^3 – y^3 + 2x^2 + 2xy
    =(x-y)(x^2+xy+y^2)+2x(x-y)
    =(x-y)(x^2+xy+y^2+2x)
    g) x^5 + x + 1
    = x^5 – x^2 + x^2 + x + 1
    = x^2( x^3 – 1) + ( x^2 + x + 1)
    = x^2( x – 1)( x^2 + x + 1) + ( x^2 + x + 1)
    = ( x^2 + x + 1)( x^3 – x^2 + 1)

    Trả lời

Viết một bình luận

Câu hỏi mới